2018
DOI: 10.1111/jgs.15556
|View full text |Cite
|
Sign up to set email alerts
|

Caregiver‐Based Interventions to Optimize Medication Safety in Vulnerable Elderly Adults: A Systematic Evidence‐Based Review

Abstract: Although some interventions improved caregiver medication knowledge and self-efficacy, effects on clinical outcomes and healthcare use were insufficiently studied. Two studies implementing collaborative care models with medication management components showed potential for improvement in quality of clinical care and reductions in healthcare visits and warrant further study with respect to medication safety. J Am Geriatr Soc 66:2128-2135, 2018.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
15
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 25 publications
2
15
0
1
Order By: Relevance
“…A systematic review of transitional care education interventions for carers of older adults who have experienced stroke found that education was effective in reducing carer burden and anxiety 13 . In another systematic review, home‐ and outpatient‐based medication reviews in the follow‐up period after hospitalization improved carers' medication knowledge and self‐efficacy 14 . Other studies have identified that carers need support with problem solving and decision‐making during the follow‐up discharge period, 15–19 support to access and navigate community‐based programmes 20–22 and support to clarify expectations of services 23 .…”
Section: Introductionmentioning
confidence: 99%
“…A systematic review of transitional care education interventions for carers of older adults who have experienced stroke found that education was effective in reducing carer burden and anxiety 13 . In another systematic review, home‐ and outpatient‐based medication reviews in the follow‐up period after hospitalization improved carers' medication knowledge and self‐efficacy 14 . Other studies have identified that carers need support with problem solving and decision‐making during the follow‐up discharge period, 15–19 support to access and navigate community‐based programmes 20–22 and support to clarify expectations of services 23 .…”
Section: Introductionmentioning
confidence: 99%
“…For example, their work has a positive impact on clinical outcomes and healthcare-resource utilization, reducing the number of hospitals visits [10] and mortality [11], and improving QoL or other patient-reported outcomes [12]. Their value has also been recognised in the care of nonhospitalised patients [13], in long-term care settings [14], and even in the delivery of home visits [15,16].…”
Section: Introductionmentioning
confidence: 99%
“…Caregivers requested that they were advised of discharge processes at admission so that they had time to process the information and think about what questions to ask. Early discharge planning (initiated during the acute phase of an illness or injury) delivered to caregivers of older adults has been shown to be effective in improving outcomes in older adults 36,37 . Given that caregivers of people with dementia experience a higher degree of burden than the caregiver of a person without dementia, 38 early pre‐discharge intervention delivered to caregivers of people with dementia may improve medication management activities post discharge.…”
Section: Discussionmentioning
confidence: 99%